Efeito nutrigenômico de extratos aquosos oriundos de alimentos cafeinados na modulação in vitro dos genes das enzimas antioxidantes - Lenz, Adriano Flesch (2015)
Beverages rich in caffeine and other biomolecules are produced from different plants, originated from different parts of the planet. Currently, coffee, green tea, black tea, yerba mate and guarana, are the five most caffeinated beverages used by human societies. In vitro and in vivo studies have been showing that these drinks have beneficial health effects such as antioxidant, anti-inflammatory, anti-obesogenic, anti-mutagenic and antitumor, including acting in the prevention of chronic diseases such as cardiovascular, neurodegenerative and cancer. However, the properties of these drinks have always been studied in isolated works, this study aims to investigate the in vitro effects of the hot aqueous extracts of five caffeinated drinks (coffee, green tea, black tea, yerba mate and guarana) on the modulation of major antioxidant enzymes genes. The aqueous extracts were prepared in a very similar way to that humans consume their daily drinks. After the bioactive compounds were quantified by highperformance liquid chromatography and the antioxidant capacity was measured via DPPH test. To analyze the cytotoxicity of the compounds and the expression of genes was performed collecting blood from healthy young subjects, the mononuclear cells were separated by Histopaque 1077 gradient and grown under controlled conditions. Cells were exposed to concentrations of 5 mg / mL of each aqueous extract, and after 6 hours of treatment, the expression of the gene pathways qRT-PCR was assessed, after the analysis of cytotoxicity via MTT. The effect of isolated caffeine, theobromine and catechin at concentrations estimated for each extract was also evaluated. Our results show quite similar composition of bioactive compounds in the extracts, as the coffee antioxidant capacity demonstrated significant results, and none of the extract showed cytotoxic activity in the MTT test. For gene expression, all extracts were able to elevate the expression of genes of the enzymes superoxide dismutase 1, catalase and glutathione peroxidase. Our results confirm previously reported results in the literature suggesting nutrigenomics action of caffeinated beverages tested here.